2023
DOI: 10.3390/metabo13090979
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organokines in Obesity and Type 2 Diabetes and Their Functions as Molecular Transducers of Nutrition and Exercise

Ji Ye Lim,
Eunju Kim

Abstract: Maintaining systemic homeostasis requires the coordination of different organs and tissues in the body. Our bodies rely on complex inter-organ communications to adapt to perturbations or changes in metabolic homeostasis. Consequently, the liver, muscle, and adipose tissues produce and secrete specific organokines such as hepatokines, myokines, and adipokines in response to nutritional and environmental stimuli. Emerging evidence suggests that dysregulation of the interplay of organokines between organs is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 330 publications
0
2
0
Order By: Relevance
“…Current evidence suggests that the release and interactions of organokines could be regulated by multiple factors, making their impact challenging to quantify. Lifestyle factors such as exercise, diet, stress, sleep, and microbiome profoundly influence organokines production, affecting disc homeostasis and susceptibility to IVDD-related diseases ( 6 , 164 166 ). Exercise, known as beneficial for IVD homeostasis, can modulate the release and activity of organ factors like irisin, ANGPTL4, osteocalcin, and adiponectin ( 113 , 167 ).…”
Section: Regulatory Factors Of Organokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that the release and interactions of organokines could be regulated by multiple factors, making their impact challenging to quantify. Lifestyle factors such as exercise, diet, stress, sleep, and microbiome profoundly influence organokines production, affecting disc homeostasis and susceptibility to IVDD-related diseases ( 6 , 164 166 ). Exercise, known as beneficial for IVD homeostasis, can modulate the release and activity of organ factors like irisin, ANGPTL4, osteocalcin, and adiponectin ( 113 , 167 ).…”
Section: Regulatory Factors Of Organokinesmentioning
confidence: 99%
“…An increasing number of studies have shown that organokines, the bioactive factors secreted by diverse tissues, may have a vital impact on disc homeostasis. The expression of organokines can be induced by several factors, including physical activity, diet, aging, and metabolic alterations like obesity and diabetes ( 5 , 6 ). Through autocrine, paracrine, or endocrine mechanisms, organokines have been linked to several inflammatory diseases, such as rheumatoid arthritis ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%